(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2018)
According to Augustin Berque, a orientalist geographer: «the space is the relationship between society and it’s environment», we can’t deny the massive role architecture has on society and the effect it has on the way we see ourselves, and in ancient times we have used architecture as a language to express our thoughts, wether we used rocks or stones or earth the point is that it was our language because it was manufactured by ourselves.These days architecture is mainly governed by pluralism and so it’s hard to see ourselves in space when its being played in the background. By studying the cases of self building from vernacular architecture (the cases of Kasbah and ksur in Morocco), to shantytowns during – modernism, creative commons and open source architecture, this dissertation explores the possbility and potentiality of an architecture governed by society and raises the question ion wether it is possible for people to use open source technology as a designing tool to create their own space.